If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + 9 = 2(x + -1) Reorder the terms: 9 + y = 2(x + -1) Reorder the terms: 9 + y = 2(-1 + x) 9 + y = (-1 * 2 + x * 2) 9 + y = (-2 + 2x) Solving 9 + y = -2 + 2x Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + y = -2 + -9 + 2x Combine like terms: 9 + -9 = 0 0 + y = -2 + -9 + 2x y = -2 + -9 + 2x Combine like terms: -2 + -9 = -11 y = -11 + 2x Simplifying y = -11 + 2x
| y-8=-4(x+7) | | 3(0.9-1)-(x+0.6)=-0.2 | | x-5=20*10 | | 1/2x+3=1/3x+2 | | m=(2-1) | | w=4+15 | | 2(x-2)=2x-6 | | 2x-8x+4=x-9+13 | | 3x-14=3x-14 | | 1.1x+8=0.5x+20 | | 1.1x+8=0.5x+29 | | (20-2x)x=90 | | 5227.50=5100(1+.025r) | | y=9.5+100 | | y=-0.62+0.0005x | | y=-0.62+0.0005211x | | y=0.0005211x+-0.62 | | 2c+4+3c=-16 | | 2x^2+1=2x+12 | | 4y-5x=40 | | .6x+1.9x=5 | | .6x+1.9=5 | | 2x^2+43x-2730=0 | | a+5=3 | | 7-6(3-8x)=0 | | x^2-14x+36= | | log(100)=10 | | ?10x+1+7x=37 | | ?10x+1+7x=32 | | ?10x+1+7x= | | ?10x+1+7x=37 | | log(x+5)-log(1-5x)=0 |